KEMAMPUAN GAYA KEPEMIMPINAN MEMODERASI PENGARUH KOMPETENSI PEGAWAI, SISTEM ADMINISTRASI KEUANGAN DAERAH, SARANA DAN PRASARANA PADA EFEKTIVITAS PENGELOLAAN KEUANGAN DAERAH KABUPATEN BADUNG - Kharismayanti, Luh Putu Utami; Widanaputra, A.A. Gede Putu; Dwirandra, A.A.N Bagus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.01.TAHUN 2018, 2018)
The purpose of this study was to find empirical evidence of a moderating influence leadership style kemapuan employee competence, the administrative system of local finance, facilities and infrastructure on the effectiveness of financial management Badung regency. This study uses quantitative and qualitative data from primary and secondary data sources collected by questionnaire distributed as many as 100 questionnaires. Moderation regression analysis is a method of data analysis used in this study. The results of this study indicate that the style of leadership able to moderate the influence of regional financial administration system and infrastructure on the effectiveness of financial management. While the style of leadership is not able to moderate the influence of employee competence on the effectiveness of financial management .